Influence of seeding rates, sowing dates, and sowing methods on field germination and plant density of winter wheat crops (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
This article presents the results of a two-year study on the effects of various combinations of seed rate, sowing dates, and sowing methods on the field germination of seeds and the productive stem stand parameters of winter wheat of the Pozitsiya Odessa variety during the fall season. Formulation of the problem. Among the key factors influencing the yield of winter grain crops are seed germination in the field and plant density. A decrease in field germination leads to uneven distribution of seedlings across the planted area and reduced plant density, which is particularly critical under low seeding rates and adverse weather conditions, as in such cases it is much more difficult for plants to compensate for sparse stands through tillering. Based on this, it is of paramount importance to develop measures aimed at achieving higher field germination rates and to establish seed rates, sowing dates, and methods that enable plants to develop adequate plant density by fall. The aim of the study was to investigate the effect of various combinations of seed rate, sowing date and sowing method on the field germination of seeds and the stem density parameters of winter wheat crops of the Pozitsiya Odessa variety during the fall season. Research methods. The study was conducted under production conditions at AGROLAND LLC in the Novomoskovsk district, Dnipropetrovsk oblast. A three-factor field experiment was set up using the split-plot design with three replications. The first-order factors were three sowing dates – at a soil temperature of 17–19 °C (first), 14–16 °C (second), and 11–13 °C (third). The second-order factors were two sowing methods: 1 – row sowing with 15 cm row spacing; 2 – strip sowing with a strip width of 12–15 cm and an inter-strip zone of 10–13 cm. The third-order plots consisted of seven seed rate variants ranging from 2.0 to 5.0 million seeds/ha, with a step size of 0.5 million seeds/ha. The area of the plot was 50.0 m². Results. Among the factors studied, only the sowing dates had a significant effect on the field germination of winter wheat seeds. It was lowest in the third sowing date treatments at a soil temperature of 11–13 °C – 72.0 % in 2024 and 74.4 % in 2025. In the first and second sowing date treatments, it was virtually the same, at 74.2 % in 2024 and 77.4 % in 2025. The total number of stems, as well as the number of stems with a diameter of 3 mm or more, was highest in the early-sown treatments at a soil temperature of 17–19 °C; at the same time, some plants in the variants with lower seeding rates formed three lateral stems, which is the better option in terms of overwintering. Crops sown in the third sowing period – at a soil temperature of 11–13 °C – had little time to develop sufficient stem density, especially at low seed rates. Based on this, the optimal option was the one where sowing was carried out at a soil temperature of 14–16 °C. Under the favorable weather conditions of the 2025 autumn growing season, due to the increased tillering potential of the winter wheat variety under study, at a seeding rate of 3.5 million seeds per hectare, the number of stems with a diameter of 3.0 cm or more, in the second sowing date variants (soil temperature at the sowing layer – 14–16 °C) was 549 stems/m², which is quite sufficient for obtaining high grain yields. Under the dry conditions of the 2024 fall growing season, the number of stems with a diameter of 3.0 mm was significantly lower than in 2025, which was due to severe drought during germination and seedling emergence. As a result, increasing the seeding rate from 4.5 to 5.0 million seeds/ha no longer resulted in a significant increase in stem numbers. In particular, in the sowing variants with a soil temperature of 14–16 °C, the average number of winter wheat stems with a diameter of 3.0 mm or more increased by only 4 stems/m² across sowing methods, or less than 1.0 %. Conclusions. In years with favorable autumn weather conditions, seeds of the winter wheat variety Pozitsiya Odesska and varieties similar to it in terms of morpho-biotype should be sown at a seeding rate of 3.5 million seeds per hectare. Under unfavo-rable weather conditions during the autumn growing season, the seeding rate for winter wheat varieties with higher tillering potential due to increased cytokinin content should be increased to 4.5 million seeds per hectare when sowing at a soil temperature of 14–19 °C (first and second sowing dates). should be increased to 4.5 million seeds per hectare.
Keywords: winter wheat; field germination; seeding rate; sowing date; sowing method; productive stems; autumn growth